CD147 promotes collective invasion through cathepsin B in hepatocellular carcinoma - Shi-Jie Wang; Dong Chao; Wei Wei; Gang Nan; Jia-Yue Li; Fen-Ling Liu; Ling Li; Jian-Li Jiang; Hong-Yong Cui; Zhi-Nan Chen (Journal of Experimental & Clinical Cancer Research, 2020)
Abstract Background Mounting evidence suggests that solid tumors display the features of collective invasion, however, the molecular mechanisms are far from clear. This study aims to verify the role and the underlying mechanisms of CD147 in collective invasion in hepatocellular carcinoma. Methods Immunostaining was used to analyze human hepatocellular carcinoma specimens and three-dimensional cultures. Three-dimensional invasion model was established to mimic in vivo invasion. RNA-sequencing was used to identify downstream effectors. Results Human hepatocellular carcinoma underwent collective invasion and CD147 was observed to be upregulated at the invasive front of tumor cell groups. CD147 was demonstrated to promote collective invasion using the modified three-dimensional invasion model, which recapitulated the main features of collective invasion. Through transcriptome analysis and enzyme activity assay, we found that CD147 enhanced cathepsin B expression and activity. Upregulated cathepsin B in hepatocellular carcinoma cells facilitated migration and invasion, which mediated CD147-induced invasive phenotype in hepatocellular carcinoma. In terms of mechanism, we found that CD147 promoted cathepsin B transcription by activating β-catenin signaling as a result of reduced GSK-3β expression. Furthermore, we found that elevated expression of CD147 as well as cathepsin B were correlated with poor prognosis in patients with hepatocellular carcinoma. Conclusions CD147 promotes hepatocellular carcinoma cells collective invasion via upregulating cathepsin B expression and targeting CD147 would be valuable for the development of novel therapeutic modalities against invasion and metastasis of cancer.